Blindness and visual impairment: quality of life and accessibility in the city of Turin - Nuzzi, Alessia; Becco, Alice; Boschiroli, Andrea; Coletto, Andrea; Nuzzi, Raffaele (Frontiers in Medicine, 2024)
Purpose: Despite the increase in socio-health conditions and in general focus on health worldwide, many diseases still adversely affect quality of life (QoL), including those causing vision loss. This study wanted to evaluate QoL of people with visual impairments through a questionnaire concerning everyday life in the urban and extra-urban areas of Turin. A personalized questionnaire including 25 questions was submitted to 100 enrolled patients. The inclusion criteria were any degree of visual impairment according to Law n. 138/2001 classification. The exclusion criteria were mental disability and residence in care homes. Lastly, statistical analysis was performed: results were classified as statistical significant with a p-value ≤0.05 or borderline (0.05